ANALISIS QUALITY OF SERVICE (QOS) JARINGAN KOMPUTER SMKN 1 TROWULAN DENGAN MENGGUNAKAN METODE PCC (PER CONNECTION CLASSIFIER) - Amzar Ashari , Akhmad; Putra Eka Prismana , IGL; Heru Mujianto , Ahmad (Inovate, 2024)
The purpose of this study is to ascertain the quality analysis's outcomes of LAN computer networks at SMKN 1 Trowulan. The Per Connection Classifier (PCC) method is used to perform quality analysis, which is intended to identify unstable or unstable network problems. Per Connection Classifier (PCC) is a technique that divides connection traffic through or in and out of a router into various groups. Src-address, dst-address, src-port, or dst-port can determine the type of this grouping. The router will save the gateway path that the data packet passes through in each connection traffic to ensure that the same gateway path will be used for subsequent packets that are still connected to the previous data packet. The outcomes of the investigation and implementation of the PCC method have resulted in better bandwidth. This happens because ISP 1 and ISP 2 traffic load is divided into two alternately taken as a whole. This prevents either ISP or modem from experiencing overload or other network problems. The throughput parameter value of 351 kb/s is in the 'Medium' category, the packet loss value is 0.086% in the 'Very Good' category, the 14.971928 ms delay value is in the 'Very Good' category, and the jitter value is 14.785288 ms in the 'Good' category. Keywords: Quality of Service (QoS), Computer Network, Per Connection Classifier (PCC) Method, Wireshark